1998
DOI: 10.1098/rspb.1998.0525
|View full text |Cite
|
Sign up to set email alerts
|

Allozyme electrophoresis as a tool for distinguishing different zooxanthellae symbiotic with giant clams

Abstract: The taxonomy of zooxanthellae in marine invertebrate symbioses is not well understood owing mainly to their lack of reliable morphological di¡erences. Nevertheless, previous work using protein and DNA electrophoreses has set the stage for advancing our taxonomic understanding of cnidarian zooxanthellae. Here we present the use of allozymes as genetic markers for distinguishing algal isolates from tridacnid hosts. Zooxanthellae from seven Tridacna and Hippopus species were isolated and maintained in axenic clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Our previous studies of the symbiotic algae from the Philippine giant clams (many of which were sequenced in the present study) demonstrated significant differences in the allozyme and RAPD patterns between symbiont isolates (Baillie et al 1998, Belda‐Baillie et al 1999, Baillie et al 2000). The likely conspecific nature of these algal isolates and their high degree of allozyme and RAPD variation suggest possible recombination in this group of clade A Symbiodinium (for more discussion, see Baillie et al 1998, 2000.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Our previous studies of the symbiotic algae from the Philippine giant clams (many of which were sequenced in the present study) demonstrated significant differences in the allozyme and RAPD patterns between symbiont isolates (Baillie et al 1998, Belda‐Baillie et al 1999, Baillie et al 2000). The likely conspecific nature of these algal isolates and their high degree of allozyme and RAPD variation suggest possible recombination in this group of clade A Symbiodinium (for more discussion, see Baillie et al 1998, 2000.…”
Section: Discussionmentioning
confidence: 48%
“…The origins, isolation, and culture of the zooxanthellae used in this study have been described previously (Baillie et al 1998, Belda‐Baillie et al 1999, Carlos et al 1999, 2000). The origins of the cultures studied are summarized, along with the GenBank accession numbers of their rDNA‐ITS sequences (Tables 1 and 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA fingerprints of zooxanthellae isolated from a frozen branch differed from fingerprints of cultures obtained from the same branch (Goulet and Coffroth 1997). Culturable dinoflagellates, however, may be rare clones or clones that have undergone genomic changes due to selection and/or mutation processes (Rowan et al 1996;Baillie et al 1998;Carlos et al 2000;LaJeunesse 2001;Santos et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wilcox et al (1999) and Baillie et al (2000), using randomly amplified polymorphic DNA (RAPD), detected within-clade variation among zooxanthellae harbored by the jellyfish Cassiopea xamachana and by giant clams, respectively. Baillie et al (1998) and Carlos et al (2000) (using allozyme analysis and temperature-gradient gel electrophoresis, respectively) found within-clade variation among zooxanthellae symbiotic with giant clams. Internal transcribed spacer (ITS) regions of nuclear DNA LaJeunesse 2001;van Oppen et al 2001) and the 23S rDNA of chloroplasts (Santos et al 2002) have also been used.…”
Section: Introductionmentioning
confidence: 99%